How to design and evaluate research in education - Fraenkel, Jack R.; Wallen, Norman E. (Boston, Massachusetts : McGraw Hill Education, 2005)
How to Design and Evaluate Research in education is directed to students taking their first course in educational research. Because this field continues to grow so rapidly with regard to both the knowledge it contains and the methodologies it employs, the authors of any introductory text are forced to carefully define their goals as a first step in deciding what to include in their book.
Part 1. Introduction to research -- Part 2. The basics of educational research --Part 3. Data analysis -- Part 4. Quantitative research methodologies -- Part 5. Introduction to qualitative research --Part 6. Qualitative research methodologies -- Part 7.Research by practitioners --Part 8. Writing research proposals and reports.
Includes bibliographical references.
Keywords: EDUCATION RESEARCH